2021
DOI: 10.1038/s41598-021-94813-1
|View full text |Cite
|
Sign up to set email alerts
|

New insights on the Ife-Ilesha schist belt using integrated satellite, aeromagnetic and radiometric data

Abstract: The present study combined analysis of satellite, aeromagnetic and radiometric data for evaluation of structural features within the Ife-Ilesha schist belt. Shuttle Radar Topographic Mission digital elevation data have been enhanced using hill-shading technique for the delineation of morphological features. The superposition of total gradient amplitude lineaments on the 3-D Euler deconvolution map revealed the trends and depth of structural features within the study region. The major trends are NE–SW, NNE–SSW,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Also, an anomaly pattern cut through Malam Mudi and Kwaimbana (north central) with detectable positive-negative anomaly pairs representing folded north-south trending structures ( Beard, 2000 ). This N–S structural imprint might have been initiated during the Pan-African orogeny ( Olasehinde et al., 1990 ; Salawu et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, an anomaly pattern cut through Malam Mudi and Kwaimbana (north central) with detectable positive-negative anomaly pairs representing folded north-south trending structures ( Beard, 2000 ). This N–S structural imprint might have been initiated during the Pan-African orogeny ( Olasehinde et al., 1990 ; Salawu et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Wright et al (1985), Ananaba andAjakaiye (1987), Caxito et al (2020) revealed that the structural grain of the Precambrian rocks in most of West Africa generally lies between the N-S, NW-SE and NE-SW. The E-W structures appear to have been produced in earlier Orogeny events (pre-Pan-African Orogeny) (Salawu et al, 2021), consequent to the dominant Pan-African Orogeny. The lineaments delineated from the HRAD and satellite imageries were superimposed on the existing faults shown on the published geological map of Nigeria for possible correlation (Figure 8).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Aeromagnetic survey and remote sensing methods are standard exploration techniques, which are highly suitable for mineral exploration programs 1,2 . Recent improvements in digital processing of remotely sensed imagery have led to higher resolution of delineation procedure of regional surface features.…”
mentioning
confidence: 99%